1999
DOI: 10.1007/s002239900679
|View full text |Cite
|
Sign up to set email alerts
|

Majority of Hip Fractures Occur as a Result of a Fall and Impact on the Greater Trochanter of the Femur: A Prospective Controlled Hip Fracture Study with 206 Consecutive Patients

Abstract: The objectives of this study were to learn how hip fracture patients fall, and to compare the mechanics of their falls with those falls that did not result in hip fracture. In this way we sought to obtain reliable insight into the etiology and pathogenesis of hip fracture and fracture prevention. A total of 206 consecutive patients with fresh hip fracture and 100 controls were interviewed and examined between October 1994 and May 1996. The only inclusion criterion was that the fracture had occurred within 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
274
1
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(299 citation statements)
references
References 28 publications
5
274
1
8
Order By: Relevance
“…The fastest-growing segment of the population is people aged 80 and over, and this group has the highest hip fracture rate. Over 95 % of hip fractures are caused by falling [16], usually by falling sideways onto the hip [17] from a standing height. While it is possible that current rates will level off or even increase, it is also possible that rates will decline faster due to broad implementation of fall prevention strategies and/or improved screening and treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…The fastest-growing segment of the population is people aged 80 and over, and this group has the highest hip fracture rate. Over 95 % of hip fractures are caused by falling [16], usually by falling sideways onto the hip [17] from a standing height. While it is possible that current rates will level off or even increase, it is also possible that rates will decline faster due to broad implementation of fall prevention strategies and/or improved screening and treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…The average age of Finnish hip fracture patients is 81.6 years for women and 76.0 years for men (Korhonen et al 2013). In Finland, the incidence of hip fractures increased up to the end of the 1990s (Kannus et al 1999) and declined thereafter (Kannus et al 2006, Korhonen et al 2013, especially among women and persons over age 65 (Korhonen et al 2013). The reasons for the decline are unclear, but better overall health and physical function, fall prevention programs, increased body weight and better osteoporosis prevention, interventions for polypharmacy, modifications of environmental hazards and increased D-vitamin intake among older people might partly explain the decline.…”
Section: Definition and Incidence Of Hip Fractures 211mentioning
confidence: 99%
“…Several finite element (FE) modeling and cadaveric experimental studies have consistently shown that a sideways fall exposes the femoral neck to the greatest risk of a fracture [7,[9][10][11][12][13]. Indeed, over 90% of hip fractures are directly caused by falls [14,15]. Therefore, if the superolateral cortical thickness could be maintained or even increased with appropriate exercise training, bone strength may be maintained and hip fracture risk reduced in old age.…”
Section: Introductionmentioning
confidence: 99%